Comparative constitutional law - Khan, Nuzhat Parveen (New Delhi, 2015)
In this book on Comparative Constitutional law an attempt has been made to discuss various aspects of different Constitutions in a comparative manner specially comparing five major Constitutions of the world such as UK, USA, Australia, Canada and India. The book is broadly covering aspects such as an understanding of Constitution and Governance, Constitutionalism, Need and Scope of Comparative Study of Constitutional Law and an understanding of various concepts such as Rule of Law, Separation of Powers, Independence of Judiciary, Judicial Review etc. Further an effort has also been made to make a comparative analysis of the aforesaid subject matter with the help of case law.
Keywords: Constitutional law